2018
DOI: 10.1002/esp.4531
|View full text |Cite
|
Sign up to set email alerts
|

Soil erodibility as impacted by vegetation restoration strategies on the Loess Plateau of China

Abstract: Near soil surface characteristics change significantly with vegetation restoration, and thus, restoration strategies likely affect soil erodibility. However, few studies have been conducted to quantify the effects of vegetation restoration strategies on soil erodibility in regions experiencing rapid vegetation restoration. This study was conducted to evaluate the effects of vegetation restoration strategies on soil erodibility, reflected by soil cohesion (Coh), penetration resistance (PR), saturated conductivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 85 publications
(353 reference statements)
1
9
0
Order By: Relevance
“…K-values increased along soil depth, which was consistent with the result of Stavi and Lai [15]. This indicated that erodibility was weakest for surface soil, and that anticorrosion ability was strongest.…”
Section: Descriptive Statistic Characteristicssupporting
confidence: 88%
See 1 more Smart Citation
“…K-values increased along soil depth, which was consistent with the result of Stavi and Lai [15]. This indicated that erodibility was weakest for surface soil, and that anticorrosion ability was strongest.…”
Section: Descriptive Statistic Characteristicssupporting
confidence: 88%
“…Therefore, k-value is regarded as an essential parameter used in soil erosion prediction [12]. Researchers have conducted a great deal of research on the k-value of soil erodibility, constructing the relationship between the k-value with soil properties and soil loss in an attempt to simplify the calculation method and analyze the spatial distribution characteristics [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Subjects such as the principles of soil erosion, soil and water conservation engineering, gully and rill erosion and desertification-combating sciences have been discussed for steep slopes, depleted fertile soil horizons, deforested areas and intensively cultivated areas, among others. Enormous resources and efforts have been invested in studies on vegetation restoration, ecological hydrology and soil and water conservation [56][57][58]. The conclusions of these studies can be summarized as follows: (i) the contribution of rainfall, soil and water conservation measurements and vegetation factors to runoff and sediment generation on loess hillslopes; (ii) establishment of different in situ and modeling methods to quantitatively describe multiple factors influencing soil moisture, runoff and soil erosion; (iii) estimation of runoff mitigation by different cover crop root systems; (iv) identification of the effects of terracing and vegetation types on soil conditions after long-term land stabilization measures have been implemented and (v) evaluation of soil carbon sequestration in arid and semi-arid degraded lands.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies [5][6][7][8][9][10][11][12] have concluded that there is a considerable increase in the hot days, warm nights at several places across the globe. Similarly, there has been considerable evidence [13][14][15][16][17][18][19][20] wherein spatio-temporal changes in extreme precipitation are observed in addition to the increasing temperature which have led to extreme droughts, flood conditions and heat waves.…”
Section: Introductionmentioning
confidence: 99%
“…Garcia-Cueto et al, [18] observed 4-5 • C and 2-3 • C rise of summer temperature increases in Northwestern Mexico under RCP 4.5 and RCP8.5, respectively. Wang et al, [19] examined the spatiotemporal trends of temperature and precipitation indices proposed by ETCCDI in the Loess Plateau region of China and observed significant warming and drying trends at all temperature and precipitation extremes, respectively. The application of ETCCDI indices in India's upper Tapi river basin has exhibited increasing trends in hottest and coldest days and decreasing trends in coldest nights in most portions of the basin [20].…”
Section: Introductionmentioning
confidence: 99%